PENGETAHUAN PETANI DALAM BUDIDAYA RUMPUT LAUT DI DESA KOLESE KKECAMATAN POASIA KABUPATEN MUNA - Susilawati, Fidar; Musadar, Musadar; Salahuddin, Salahuddin; Malik, Nurhayu (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
Seaweed cultivation is a farming business that requires the ability to manage it in order to get good results. Based on a survey conducted in Kolese Village, Pasikolaga Subdistrict, Muna Regency, problems related to seaweed cultivation were found, namely seaweed farmers in the College village had not been able to control pests and diseases in seaweed, did not have the technical expertise for good cultivation. Researchers suspect the cause is the lack of knowledge of seaweed farmers regarding seaweed cultivation. This study aims to find out how farmers know about seaweed cultivation in Kolese Village, Pasikolaga District, Muna Regency. The variable in this study is farmer knowledge, this research was conducted in December-January 2023. The population in this study were all seaweed farmers in Kolese Village, Pasikolaga District, totaling 22 people with research samples through the census method. This type of research is Quantitative research using primary and secondary data sources, data collection techniques in this study were observation, interviews and questionnaires, and data analysis used in this study was quantitative descriptive analysis. The results of this study indicate that most of the seaweed farmers in Kolese Village have high knowledge about planting, selecting seeds and harvesting. Some farmers also understand and are able to apply seaweed cultivation methods well.